Reengineering of Manufacturing Business Process Utilising the Manufacturing Module of an ERP Application - Pratama, I Putu Agastya Harta; Sukarsa, I Made; Putri, Gusti Agung Ayu (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
The significant change in the consumption pattern of Indonesia’s modernising society––further intensified by the Indonesian Government’s plan to push towards the era of the Industrial Revolution 4.0, has fostered the need for manufacturing companies to create newly automated processes and make the transition to become a digitalised business entity. Enterprise Resource Planning is a software that enables the creation of integration and automation of business processes between various departments within a company, thus creating an effective business strategy. The data that has been acquired from research at a poultry processing company are then being mapped into the ERP software of Odoo V12.0, therefore creating new sets of re-engineered business processes. There are seven newly proposed reengineering business processes––in which only concentrate on the production and technical department within the particular company, by utilising the manufacturing and maintenance modules. The re-engineered business processes are assessed using the Technology Acceptance Model theory, to measure its usability and practicality, which generates the score of Likert’s interpretation above the accepted standard of 1340 and 1227, for both the manufacturing and maintenance modules respectively.  Keywords: Business Process Reengineering, Enterprise Resource Planning, Manufacturing  Process, Odoo, Technology Acceptance Model.